Battling the tropics to settle a nation: Negotiating multiple energies, frontiers and feedback loops in Australia. (July 2018) - Rickards, Lauren; Oppermann, Elspeth
Abstract: Multiple forms and spaces of energy are enrolled in nation-building projects. In this cross-disciplinary paper, we outline how struggles to govern the relations between climate and the human body have shaped nation-building efforts and electricity infrastructure in the settler-colonial society of Australia. Focused on Australia's tropical zone, notably the hot, recalcitrant, militarized region of the Northern Territory, we explore how questions of climate have slowed, undone and accelerated efforts to securely settle its capital city, Darwin. In doing so, we highlight the multiple links between electricity infrastructure and air-conditioning that have made it possible to hold 'climate' and 'body' together, co-producing indoor microclimates and habitable territory while contributing to the warming climate that is now raising questions about the limits of this electricity-enabled habitability. By examining the intersecting spatialities of electricity, we help advance more 'thoroughly geographical' (Bridge, 2018) accounts of the relation between energy infrastructures and nation-building, highlighting the multiple forms, frontiers and feedback loops through which energy – broadly defined, as foundational category – acts as hindrance, enabler and side-effect of nation-building projects. We show how this perspective reveals troubling paradoxes and tensions, including accelerating feedbacks between energy use and climate change extending far beyond Australia's borders.